Species distribution and screening of Trypanosoma DNA in phlebotomine sand flies from four southern provinces of Thailand - Nantatchaporn Klaiklueng; Rawadee Kumlert; Sopavadee Moonmake; Toon Ruang-areerate; Padet Siriyasatien; Sakone Sunantaraporn; Darawan Wanachiwanawin; Pichet Ruenchit; Sirichit Wongkamchai (Current Research in Parasitology and Vector-Borne Diseases)
Sand flies are principal vectors of Leishmania spp. and Trypanosoma spp. Identifying precise vector species is crucial for effective control. We conducted a study on the species distribution of phlebotomine sand flies in cave-dwelling and non-cave-dwelling in four southern provinces of Thailand. In this study, we collected 621 sand flies (346 females and 275 males) and identified all specimens based on morphology and DNA barcoding, employing cytochrome c oxidase subunit 1 (cox1) and cytochrome b (cytb) genes. In female specimens, we also screened the small subunit 18S ribosomal RNA (18S rRNA) gene for Leishmania spp. and Trypanosoma spp. Morphologically, 467 (75.2%) sand flies were identified to species level, 47 (7.57%) to subgenus level, and 107 (17.23%) to genus level. These included Idiophlebotomus asperulus (43.48%), Sergentomyia khawi (26.73%), S. anodontis (2.25%), S. brevicaulis (2.25%), Grassomyia indica (0.48%), Phlebotomus (Euphlebotomus) spp. (4.83%), Phlebotomus (Lewisius) spp. (2.74%), Sergentomyia spp. (9.18%), and Phlebotomus spp. (8.05%). Among the 107 specimens identified to genus level, DNA barcoding further identified 49 (45.79%) as Sergentomyia barraudi (1.61%), S. bailyi (0.16%), Phlebotomus kiangsuensis (2.9%), and Ph. stantoni (1.61%). No Leishmania DNA was detected, but Trypanosoma DNA was found in females of S. khawi from Narathiwat Province. Expanding genetic reference databases of sand flies located in four provinces of southern Thailand will improve barcoding accuracy. Understanding sand fly species composition and distribution is imperative for vector control and disease prevention in Thailand.